2011
DOI: 10.1088/0004-6256/142/4/131
|View full text |Cite
|
Sign up to set email alerts
|

The Canada-France Ecliptic Plane Survey—full Data Release: The Orbital Structure of the Kuiper Belt

Abstract: 7We report the orbital distribution of the trans-neptunian objects (TNOs) discovered during the Canada-France Ecliptic Plane Survey (CFEPS), whose discovery phase ran from early 2003 until early 2007. The follow-up observations started just after the first discoveries and extended until late 2009. We obtained characterized observations of 321 sq.deg. of sky to depths in the range g ∼23.5 -24.4 AB mag. We provide a database of 169 TNOs with high-precision dynamical classification and known discovery efficiency.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
317
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(333 citation statements)
references
References 67 publications
(156 reference statements)
15
317
1
Order By: Relevance
“…In previous studies (e.g., Brown 2001; Gulbis et al 2010;Petit et al 2011;Gladman et al 2012), this functional form for the inclination distribution has been used to model the intrinsic inclination distribution of the Kuiper Belt, and different values of the Gaussian standard deviation, σ, have been derived for different dynamical classes of KBOs. We note, however, that the intrinsic distribution of Ω will not actually be uniformly random if the population's mean plane deviates from the chosen reference plane.…”
Section: Uncertainty Of the Measured Mean Planementioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies (e.g., Brown 2001; Gulbis et al 2010;Petit et al 2011;Gladman et al 2012), this functional form for the inclination distribution has been used to model the intrinsic inclination distribution of the Kuiper Belt, and different values of the Gaussian standard deviation, σ, have been derived for different dynamical classes of KBOs. We note, however, that the intrinsic distribution of Ω will not actually be uniformly random if the population's mean plane deviates from the chosen reference plane.…”
Section: Uncertainty Of the Measured Mean Planementioning
confidence: 99%
“…With the methods described in the previous section, we find that the mean plane of this population has J2000 ecliptic-equinox inclination and longitude of ascending node i 1 . 8 Gulbis et al 2010;Petit et al 2011Petit et al , 2017. We generated 40,000 simulated sets of 769 objects with the same semimajor axes as the real classical KBOs.…”
Section: The Mean Plane Of the Classical Kuiper Beltmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 10 and 30 AU, OCC dust is predicted to be dominant, with some additional contributions (∼10-20%) from both JFC and EKB dust. Finally, at distances greater than 30 AU the EKB dust dominates, reflecting the near-by location of the EKB parent bodies themselves (e.g., Petit et al 2011). One can also see the very large discrepancy between the extrapolated Grün et al (1985) model prediction and the total flux found in Poppe (2016), with the latter typically an order-of-magnitude less than the former.…”
Section: Figmentioning
confidence: 92%